Multi-Wafer Rotating MEMS Machines Turbines, Generators, and Engines - Lang, Jeffrey; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Multi-Wafer Rotating MEMS Machines: Turbines, Generators, and Engines is an outgrowth of the MIT Micro Engine Project. This project began at the Massachusetts Institute of Technology in the Fall of 1995, and later expanded through collaborations with the Georgia Institute of Technology, the Clark Atlanta University, and the University of Maryland at College Park. The overall objective of the Micro Engine Project was to develop a small but power-dense gas turbine generator based on MEMS fabrication technologies. Thus, the project sought to develop a fuel-burning jet engine that would drive an electric generator to produce electric power for general purpose use. Along the way, the project would advance the science and engineering of many disciplines from the MEMS perspective. The Micro Engine Project was by its very nature a highly mult-disciplinary project pursuing advances in materials, structures, fabrication, combustion, heat transfer, turbomachinery, bearings and electromechanics, all at the MEMS scale. Many of these topics are addressed in this volume, including: materials structures and packaging multi-wafer MEMS fabrication and and bonding technologiesElectroplating magnetic components electroplating magnetic structures into silicon very-high-speed air bearings thermofluids and turbomachinery electric and magnetic generators combustion About The MEMs Reference Shelf: "The MEMs Reference Shelf is a series devoted to Micro-Electro-Mechanical Systems (MEMs) which combine mechanical, electrical, optical, or fluidic elements on a common microfabricated substrate to create sensors, actuators, and microsystems. The series, authored by leading MEMs practitioners, strives to provide a framework where basic principles, known methodologies and new applications are integrated in a coherent and consistent manner." STEPHEN D. SENTURIA Massachusetts Institute of Technology, Professor of Electrical Engineering, Emeritus
to PowerMEMS -- System Design Considerations and Device Overview -- Materials, Structures and Packaging -- Microengine Fabrication -- Fabrication of Microscale Rotating Magnetic Machines -- High-Speed Gas Bearings for Micro-Turbomachinery -- Thermofluidics and Turbomachinery -- Motors and Generators -- Microcombustors for Rotating Machinery.
Keywords: Engineering; Computer engineering; Electronics; Systems engineering; Electric engineering; Engineering; Electronics and Microelectronics, Instrumentation; Energy Technology; Circuits and Systems; Electrical Engineering; Energy, general